Strategi Pembelajaran Irex Dalam Meningkatkan Keterampilan Menulis Siswa Kelas II SD Negeri 0513 Aek Lancat - Siregar, Lina Mayasari; Pohan, Sahrul; Siregar, Lailan Aprina (Yayasan Perguruan Kampus, 2025)
The purpose of this research is to determine (1) Writing Skills of Class II Students at SD Negeri 0513 Aek Lancat. (2) Application of the irex learning strategy in improving the writing skills of class II students at SD Negeri 0513 Aek Lancat.The type of research used is Classroom Action Research (PTK). This research was carried out in class IV of SD Negeri 0513 Aek Lancat. The data analysis techniques in this research are qualitative and quantitative data analysis techniques. Based on the results of the pre-cycle students' writing skills, the low category was 8.33% of students' writing skills were very good, 2 or 16.67% of students' writing skills were